2010
DOI: 10.1002/anie.201004310
|View full text |Cite
|
Sign up to set email alerts
|

Heteronuclear NMR Correlations To Probe the Local Structure of Catalytically Active Surface Aluminum Hydride Species on γ‐Alumina

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
76
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(84 citation statements)
references
References 28 publications
8
76
0
Order By: Relevance
“…The signal at 26 ppm assigned to Al–CH 2 – C H–( C H 3 ) 2 is no longer detected. The broad 1 H signal at 4.3 ppm is attributed to Al– H , 43 Si– H and Si H 2 . 55 , 56 , 68 …”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…The signal at 26 ppm assigned to Al–CH 2 – C H–( C H 3 ) 2 is no longer detected. The broad 1 H signal at 4.3 ppm is attributed to Al– H , 43 Si– H and Si H 2 . 55 , 56 , 68 …”
Section: Resultsmentioning
confidence: 97%
“…43 We were interested in the formation of aluminum hydride species through a variable temperature treatment (100 °C to 400 °C, rate 60 °C h –1 , Fig. S8 and S9, ESI†) under high vacuum (10 –5 mbar).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The choice of decoupling scheme depends upon the type of heteronuclear interactions that broadens the spectral lines [15,16]. It has been shown that the heteronuclear scalar coupling between nuclei with spin quantum number I = ½ spin and surrounding quadrupolar nuclei (I > 1/2) with half-integer spin quantum number can dramatically decrease the spectral resolution and hinder the extraction of structural and chemical information [16][17][18][19][20][21]. Although the heteronuclear dipolar coupling can, in principle, be averaged by MAS, the introduction of other time-dependent phenomena, such as RF irradiation (as applied during a decoupling sequence for example), can lead to an interference effect if the two happen on a similar timescale.…”
Section: Introductionmentioning
confidence: 99%